1966
DOI: 10.1172/jci105459
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of kynurenine excretion with liver tryptophan pyrrolase levels in disease and after hydrocortisone induction.

Abstract: In a large variety of apparently unrelated diseases, the major pathway of tryptophan metabolism, that which proceeds through kynurenine, has been observed to be abnormal. The deviation is a quantitative one: the urinary excretion of one or more normal metabolites is high. Attempts to explain this phenomenon have largely been restricted to hypotheses that assume a "metabolic block" in the catabolism of these metabolites, as exemplified by pyridoxine deficiency. However, it seems unlikely that the variety of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

1968
1968
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(60 citation statements)
references
References 20 publications
2
58
0
Order By: Relevance
“…This equilibrium is lost under conditions of stress (5,6,34,36), and the degree of deviation depends on both the type of stress experienced and the patient. Two types of neonatal stress, prematurity and fetal distress, were studied here.…”
Section: Discussionmentioning
confidence: 99%
“…This equilibrium is lost under conditions of stress (5,6,34,36), and the degree of deviation depends on both the type of stress experienced and the patient. Two types of neonatal stress, prematurity and fetal distress, were studied here.…”
Section: Discussionmentioning
confidence: 99%
“…However this explanation would imply the extremely unlikely possibility that all tryptophan degradative enzymes distal to TP had a similar or identical rhythmic pattern. In this context Altman and Greengard (1) indicated that at times of elevated TP activity the kynurenine degradative enzymes, kynureninase, kynurenine hydroxylase, and kynurenine transaminase, become rate-limiting; While it is functionally possible to exceed the capacity of these enzymes to degrade kynurenine, the products of these enzymes as measured herein varied in the same diurnal fashion as did kynureCircadian Periodicity of Tryptophan Metabolism nine itself. The fact that the ratios of these metabolites were somewhat dissimilar may indeed suggest that enzymes subsequent to TP become ratelimiting during the period of maximal TP activity.…”
Section: Resultsmentioning
confidence: 73%
“…Recent studies in which liver biopsies were obtained showed that TP in humans could also be induced by pharmacologic quantities of adrenal glucocorticoids (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, liver biopsy was necessary to determine pyrrolase activity but recently an indirect method which is almost as effective has become available. After a small dose of L-tryptophan the excretion of kynurenine, a metabolite of tryptophan resulting from pyrrolase activity, is almost proportional to pyrrolase activity of biopsied liver material (1).…”
mentioning
confidence: 99%